Halloysite nanotubes loaded with nano silver for the sustained-release of antibacterial polymer nanocomposite scaffolds. (1st June 2020) - Guo, Wang; Liu, Wei; Xu, Li; Feng, Pei; Zhang, Yanru; Yang, Wenjing; Shuai, Cijun
Abstract: It is challenging for antibacterial polymer scaffolds to achieve the drug sustained-release through directly coating or blending. In this work, halloysite nanotubes (HNTs), a natural aluminosilicate nanotube, were utilized as a nano container to load nano silver (Ag) into the lumen through vacuum negative-pressure suction & injection and thermal decomposition of silver acetate. Then, the nano Ag loaded HNTs (HNTs@Ag) were introduced to poly-l -lactic acidide) (PLLA) scaffolds prepared by additive manufacturing for the sustained-release of Ag + . Acting like a 'shield', the tube walls of HNTs not only retarded the erosion of external aqueous solution on internal nano Ag to generate Ag + but also postponed the generated Ag + to diffuse outward. The results indicated the PLLA-HNTs@Ag nanocomposite scaffolds achieved a sustained-release of Ag + over 28 days without obvious initial burst release. Moreover, the scaffolds exhibited a long-lasting antibacterial property without compromising the cytocompatibility. Besides, the degradation properties, biomineralization ability and mechanical properties of the scaffolds were increased. This study suggests the potential application of inorganic nanotubes as drug carrier for the sustained-release of functional polymer nanocomposite scaffolds.